Coming down from the trees: is terrestrial activity in Bornean orangutans natural or disturbance driven? - Ancrenaz, M.; Sollmann, R.; Meijaard, E.; Hearn, A.J; Ross, J; Samejima, H; Loken, B; Cheyne, S.M; Stark, D.J; Gardner, P.C; Goossens, B.; Mohamed, A; et al. (Springer, 2014)
The orangutan is the world's largest arboreal mammal and images of the red ape moving through the tropical forest canopy symbolise its typical arboreal behaviour. Records of terrestrial behaviour are scarce and often associated with habitat disturbance. We conducted a large-scale species-level analysis of ground-based camera-trapping data to evaluate the extent to which Bornean orangutans Pongo pygmaeus come down from the trees to travel terrestrially and whether they are indeed forced to the ground primarily by anthropogenic forest disturbances. Although the degree of forest disturbance and canopy gap size influenced terrestriality, orangutans were recorded on the ground as frequently in heavily degraded habitats as in primary forests. Furthermore, all age-sex classes were recorded on the ground (flanged males more often). This suggests that terrestrial locomotion is part of the Bornean orangutan's natural behavioural repertoire to a much greater extent than previously thought and is only modified by habitat disturbance. The capacity of orangutans to come down from the trees may increase their ability to cope with at least smaller-scale forest fragmentation and to cross moderately open spaces in mosaic landscapes, although the extent of this versatility remains to be investigated.